\(\left(x-7\right)\left(x+3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-7=0\\x+3=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=7\\x=-3\end{matrix}\right.\)
Vậy \(S=\left\{7;-3\right\}\)
\(\left(x-7\right)\left(x+3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-7=0\\x+3=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=7\\x=-3\end{matrix}\right.\)
Vậy \(S=\left\{7;-3\right\}\)
A) 2x³+6x²=x²+3x
B) (2x+5)²=(x+2)²
C) x²-5x+6=0
D) (2x-7)²-6(2x-7)(x-3)=0
E) (x-2)(x+1)=x²-4
G) 2x(2x-3)=(3-2x)(2-5x)
H) (1-x)(5x+3)=(3x-7)(x-1)
F) (x+6)(3x-1)+x+6=0
I) (4x-1)(x-3)=(x-3)(5x+2)
K) (x+4)(5x+9)-x-4=0
H) (x+3)(x-5)+(x+3)(3x-4)=0
M) (2x+3)(-x+7)=0
Tìm x,y :
a)(y-2).(y-3)+(y-2)-1=0
b)x^3+27+(x+3).(x-9)=0
c)2(x+3)-x^2-3x=0
d)(x-7).(x+3)=(x+3.(2x-9)=0
e)36-x^2+2x-1=0
Dạng 2 : Tìm x Bài 1: Tìm x biết :
a) ( x – 16 ) – 74 = 0 b) (3 x – 5) .7 mũ 3 = 7 mũ 4
c) 560 – 13x = 365 d) 275 – 7( x + 1) = 100
e) 3 x 7 14 3.2 mũ 3 f) 7x – 49 = 105
g) 5x – 16 = 14 h) 3x – 138 = 23 . 2 2
A(2,3x-6,5)(0,1x+2)=0
B(2x+7)(x-5)(5x+1)=0
C(x-1)(2x+7)(x2+2)=0
D(4x-10)(24+5x)=0
E(3,5-7x)(0,1x+2,3)=0
F (5x+2)(x+7)=0
G15 (x+9)(x-3)(x+21)=0
H (x2+1)(×2-4x+4)=0
I(3x-2)(2 (x+3)/9-4x-3/5)=0
c) C = x(y2 +z2)+y(z2 +x2)+z(x2 +y2)+2xyz.
d) D = x3(y−z)+y3(z−x)+z3(x−y).
e) E = (x+y)(x2 −y2)+(y+z)(y2 −z2)+(z+x)(z2 −x2).
b) x2 +2x−24 = 0.
d) 3x(x+4)−x2 −4x = 0.
f) (x−1)(x−3)(x+5)(x+7)−297 = 0.
(2x−1)2 −(x+3)2 = 0.
c) x3 −x2 +x+3 = 0.
e) (x2 +x+1)(x2 +x)−2 = 0.
a) A = x2(y−2z)+y2(z−x)+2z2(x−y)+xyz.
b) B = x(y3 +z3)+y(z3 +x3)+z(x3 +y3)+xyz(x+y+z). c) C = x(y2 −z2)−y(z2 −x2)+z(x2 −y2).
Bài 4: Tìm x, biết.
a) 4x(x - 7) - 4x2 = 56
b) 12x(3x - 2) - (4 - 6x) = 0
c) 4(x - 5) - (5 - x)2 = 0
d) x(x +1) - x(x - 3) = 0
e) - 6x + 8 = 0 f) 2 + 2x + = 0
tìm x biết
a)5x(x-3)+7(x-3)=0
b)x^2017=x^2018
c)2x^2=x
d)x^3+x^2=0
e)x^5=x^4
A) 2x³+6x²=x²+3x
B) (2x+5)²=(x+2)²
C) x²-5x+6=0
D) (2x-7)²-6(2x-7)(x-3)=0
E) (x-2)(x+1)=x²-4
G) 2x(2x-3)=(3-2x)(2-5x)
H) (1-x)(5x+3)=(3x-7)(x-1)
F) (x+6)(3x-1)+x+6=0
I) (4x-1)(x-3)=(x-3)(5x+2)
K) (x+4)(5x+9)-x-4=0
H) (x+3)(x-5)+(x+3)(3x-4)=0
Help me
A) 2x³+6x²=x²+3x
B) (2x+5)²=(x+2)²
C) x²-5x+6=0
D) (2x-7)²-6(2x-7)(x-3)=0
E) (x-2)(x+1)=x²-4
G) 2x(2x-3)=(3-2x)(2-5x)
H) (1-x)(5x+3)=(3x-7)(x-1)
F) (x+6)(3x-1)+x+6=0
I) (4x-1)(x-3)=(x-3)(5x+2)
K) (x+4)(5x+9)-x-4=0
H) (x+3)(x-5)+(x+3)(3x-4)=0